Omni-Channel Service Analysis of Purchase Intention - Sugiat, Maria; Saabira, Nadia; Witarsyah, Deden (Society of Visual Informatics, 2023)
The COVID-19 pandemic has caused a decline in various aspects of the economy, including the fashion sector. Many fashion retailers have closed, so sales have fallen. However, many retailers can also adapt and change using new communication channels. This change presents new challenges for fashion companies and retailers to integrate channels into omnichannel services. This study aims to analyze the factors influencing customer behavior in omnichannel services through their intention to accept and use new technology in shopping. This study adopts the UTAUT2 model by adding two new variables: personal innovation and perceived security. This model was tested on 353 samples from Uniqlo customers residing in Indonesia. This research method uses a Quantitative PLS-SEM approach. This study tested the outer model, inner model, and hypothesis t-test with a bootstrap procedure using SmartPLS software. The results showed that the performance expectation factor did not affect the omnichannel purchase intention variable because the t-statistic value is less than 1.65. Meanwhile, other factors such as effort expectation, social influences, habits, hedonic motivation, perceived security, and personal innovativeness affect omnichannel purchase intentions because the t-statistic value is more than 1.65. The most positive and significant factor is personal innovativeness. Based on the results of this study, it is revealed that digitalization creates challenges for companies in maintaining digital businesses. Through various omnichannel service channels, this research can identify the factors influencing consumers' purchase intention